Peste des Petits Ruminants Virus Fusion and Hemagglutinin Proteins Trigger Antibody-Dependent Cell-Mediated Cytotoxicity in Infected Cells - Rojas, José M.; Rodríguez-Martín, Daniel; Avia, Miguel; Martín, Verónica; Sevilla, Noemí (Frontiers in Immunology, 2019)
The adaptive immune system utilizes multiple effector mechanisms to clear viral infections. Among those antibody-dependent cell-mediated cytotoxicity (ADCC) can help recognize and clear virus-infected cells. In the present work we evaluated ADCC contribution to immunity in two economically important viral diseases that affect ruminants: bluetongue and peste des petits ruminants. Immune sera obtained from sheep experimentally infected with bluetongue virus (BTV) serotype 8 or peste des petits ruminant virus (PPRV) IC’89 were used for this study. PPRV immune sera could bind to the surface of PPRV-infected ovine B cells while BTV immune sera was unable to bind to the surface of BTV-infected sheep cells but could recognize intracellular BTV antigens. BTV and PPRV immune serum ADCC potency was established using an ovine autologous cytotoxicity assay that employed an NK cell-enriched fraction as effector cells and a virus-infected B cell-enriched fraction as target cells. In this system, immune sera triggered ADCC against PPRV-infected cells, but not against BTV-infected cells. PPRV immune sera could recognize PPRV fusion and hemagglutinin proteins on the surface of transfected cells, and enhanced lysis of these cells in ADCC assays. This indicated that these viral antigens are natural ADCC targets during PPRV infection. The present work describes a novel effector immune mechanism against PPRV in the natural host that could contribute to virus clearance highlighting the importance of studying protective immune mechanisms to improve current vaccines by invoking all effector arms of immunity.